Comparing the removal performance of CO2 gas using adsorption and absorption techniques - Nurulhaida, Luhid (2008)
Over the past century, the Earth has increased in temperature by about 5 °C and this is because of an increase in concentration of the main greenhouse gases; carbon dioxide. Therefore, a modification of gas phase of adsorption-absorption process was used. In the recent research, this technique was established by using a single adsorbent. To compare the effect of changing the gas removal techniques and to study the performance on the CO gas removal from different adsorbent, Gas Absorption Adsorption Unit was used with granular activated carbon and zeolites as the adsorbents. For this purpose, purified CO 2 was used. This study was conducted using various gas flow rate (100, 75 and 50 m2 3/hr) and water flow rate (250 and 200 L/hr). The experiment had been run twice at different condition; with present and absent of zeolites. At the end of the study, it was observed that increasing of gas flow rate reduce the composition of CO dissolved in the water. On the other hand, increasing the water flow rate will increase the composition of CO2 dissolved in the water solution. Beside that, higher gas flow rate increases the efficiency of the process. Increasing of water flow rate will increase the CO2 2 composition dissolved even greater rather than increasing gas flow rate. The CO composition dissolved in water is decrease with the present of zeolites. This shows that by having zeolites, it helps to decrease the rate of absorption of C02 2.The process will be more efficient if the CO2 composition in the receiving vessel is high.